Effectiveness of patients with liver cirrhosis treatment by cleaned asycytic liquid reinfusion - Dzygal, O. F. (Journal of Education, Health and Sport, 2017)
The clinical manifestation of liver cirrhosis (LC) in patients is often complicated, for example, by the cirrhotic syndrome, which is accompanied by free fluid accumulation in the abdominal cavity. One of the likely ways to improve the clinical condition of such patients is the purified ascetic fluid (AF) reinfusion. The efficacy of 48 patients with LC complicated by ascites treatment was retrospectively analyzed. These patients were undergone laparocentesis, their AF was purified using the original device and reinfused. The expressed efficacy of purified AF reinfusion in patients with LC complicated by ascites was shown. One should take into consideration only additional method of treatment of the named contingent of patients using purified AF reinfusion, since in this case we only gain time before performing the surgery. According to majority of treated patients clinical condition improvement after AF reinfusion the author argues that complex follow-up treatment of the underlying disease may include single-step surgical interventions and minimally invasive surgical interventions. Conclusion was made about the purified AF reinfusion reasonability with the therapeutic purposes in patients with LC complicated by ascites. It is well tolerated in most cases and contributes to the improvement of the patients with LC clinical manifestation.